2008
DOI: 10.1073/pnas.0803047105
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Tsc2 in pancreatic β cells induces β cell mass expansion and improved glucose tolerance in a TORC1-dependent manner

Abstract: Regulation of pancreatic ␤ cell mass and function is a major determinant for the development of diabetes. Growth factors and nutrients are important regulators of ␤ cell mass and function. The signaling pathways by which these growth signals modulate these processes have not been completely elucidated. Tsc2 is an attractive candidate to modulate these processes, because it is a converging point for growth factor and nutrient signals. In these experiments, we generated mice with conditional deletion of Tsc2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
161
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(178 citation statements)
references
References 38 publications
16
161
1
Order By: Relevance
“…These changes are explained by increases in β-cell mass, proliferation and cell size. 7 A separate study demonstrated that conditional Tsc2 deletion in β cells exhibited a similar phenotype, but these mice developed diabetes and β-cell failure after 40 weeks. 8 The differences in the phenotype between these reports are most likely explained by different genetic backgrounds and the RIP-Cre line (hypothalamic expression) used.…”
Section: Evidence From Genetic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes are explained by increases in β-cell mass, proliferation and cell size. 7 A separate study demonstrated that conditional Tsc2 deletion in β cells exhibited a similar phenotype, but these mice developed diabetes and β-cell failure after 40 weeks. 8 The differences in the phenotype between these reports are most likely explained by different genetic backgrounds and the RIP-Cre line (hypothalamic expression) used.…”
Section: Evidence From Genetic Modelsmentioning
confidence: 99%
“…mTORC1 controls growth (cell size), proliferation (cell number) and metabolism directly, by modulating eukaryotic initiation factor 4E-binding proteins (4E-BP 1, 2 and 3) and ribosomal protein S6 kinases (S6K 1 and 2), and indirectly, by attenuating AKT signaling via an mTORC1/ S6K-mediated negative feedback loop. [1][2][3][4][5][6][7][8][9][10] How TSC/mTOR signaling regulates β-cell mass expansion is not completely understood. A better understanding of how mTORC1 regulates β-cell mass and the role of interactions between mTORC1 and other signaling pathways in this process are critical to discovering how β-cell mass adapts to insulin resistance and autoimmune injury and, ultimately, how it impacts diabetes management.…”
Section: Introductionmentioning
confidence: 99%
“…110 Hence, mTORC1 signaling is actually a critical mediator of cellular adaptation to nutrient overload and increased insulin demand during diet-induced obesity, which is a conclusion further confirmed by genetically inducing mTORC1 overactivity within b-cells. 98,99,111 Nevertheless, these recent published data also highlight how much remains to be done to better understand the role of the mTORC1 pathway in the physiopathology of obesity and other metabolic diseases. The evidence reported so far clearly suggests that it might be counterproductive to broadly target the mTORC1 pathway for the treatment of obesity and obesity-related metabolic alterations, such as hyperlipidemia, glucose intolerance and insulin resistance.…”
Section: Mtorc1 Signaling and The Regulation Of Peripheral Metabolismmentioning
confidence: 99%
“…Indeed, in vivo overactivity of mTORC1 signaling, due to deletion of either TSC2 (a negative regulator of mTORC1) or loss of LKB1 (a positive regulator of AMPK) in b-cells, increases b-cell mass and improves glucose tolerance. 98,99 Conversely, rapamycin treatment leads to inhibition of b-cell proliferation and apoptosis, 100,101 and worsens hyperglycemia in obese animals by inhibiting glucose-stimulated insulin secretion. 102,103 mTORC1 in the liver As expected, once activated, mTORC1 signaling has a positive effect on hepatocyte growth, protein synthesis and cell cycle, and hence contributes to liver regeneration.…”
Section: Mtorc1 Signaling and The Regulation Of Peripheral Metabolismmentioning
confidence: 99%
See 1 more Smart Citation